(untitled) - Brinkley, Captain F. (Boston, 1902)
This book introduce about history of the military epoch. Manners and customs of the military epoch. Weapons and operations of war during the military epoch. Bushi-Do oe the way of the warrior. Refinements and pastimes of the military epoch.
Keywords: Nhật Bản,Japan; Lịch sử,History